1987
DOI: 10.1128/iai.55.1.245-252.1987
|View full text |Cite
|
Sign up to set email alerts
|

Purification, partial characterization, and identification of a skin-reactive protein antigen of Mycobacterium bovis BCG

Abstract: An immunogenic and skin-reactive protein called P64 was purified from Sauton zinc-deficient culture filtrate of Mycobacterium bovis BCG by using successively hydrophobic chromatography on phenyl-Sepharose, ion exchange on DEAE-Sephacel, and molecular sieving on Sephadex G-200. The final P64 preparation was found to be homogeneous based on several analyses. Protein P64 was a constituent of BCG cells since it was present in soluble cellular extract from normally grown BCG cells. It represented 8 to 9% of the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…In vitro observations indicate furthermore that members of the HSP60 family might have intrinsic capacity to induce release of proinflammatory cytokines from human monocytic cells [23], and this may further add to tissue destruction. Significant amounts of bacterial HSPs may be encountered in the subgingival milieu because the molecules have been found in bacterial culture supernatants [24]. In sum, HSPs from bacteria in dental plaque might also have the potential to contribute to the development of inflammation and the tissue damage found in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro observations indicate furthermore that members of the HSP60 family might have intrinsic capacity to induce release of proinflammatory cytokines from human monocytic cells [23], and this may further add to tissue destruction. Significant amounts of bacterial HSPs may be encountered in the subgingival milieu because the molecules have been found in bacterial culture supernatants [24]. In sum, HSPs from bacteria in dental plaque might also have the potential to contribute to the development of inflammation and the tissue damage found in periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, culture filtrate (CF) and cytoplasmic extract were prepared from 2-week-old cultures of zinc-supplemented M. bovis BCG (GL2). Native Ag85 (30-32 kDa) and heat-shock protein 65 (hsp 65; GroEL related 65 kDa) were purified from zinc-supplemented and zinc-deprived M. bovis BCG culture filtrate, respectively, by sequential chromatography on phenyl-Sepharose, DEAE-Sephacel and Sephadex [11,12].…”
Section: Methodsmentioning
confidence: 99%
“…More unexpected was the finding that the Cpn60 proteins from mycobacteria appear not to exist as stable large oligomers. Early work on what subsequently proved to be the Cpn60.1 protein of M. bovis BCG showed that it had a subunit molecular mass of c. 65 kDa but purified as a complex of c. 250 kDa, corresponding roughly to a tetramer (de Bruyn et al, 1987). Moreover, both of the Cpn60 proteins from M. tuberculosis when purified formed only low molecular weight structures, probably monomers or dimers .…”
Section: Multiple Chaperonin Genes In the Actinobacteriamentioning
confidence: 99%